2014
DOI: 10.9753/icce.v34.structures.41
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Tsunami Pressure Acting on Piloti-Type Buildings

Abstract: It is known that piloti-type structures, which have an open space on the ground floor, have advantages for tsunami hitting because tsunami can pass through the ground floor. There is a basic guideline for the design of piloti-type structures for tsunami forces but detailed information such as tsunami forces acting on the elevator hall or the ceiling is not speculated. Then, the hydraulic physical model tests were performed by using a newly-developed tsunami wave generator. As a result of the physical model tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Palermo et al [10] described the tsunami-induced force components on nearshore structures and reported that the hydrodynamic and surge components were a function of the instantaneous velocity and water depth. Other studies focused on the experimental testing of tsunami bore loads on rectangular buildings [11], piloti-type buildings [12], walls with overhangs [13] and coastal bridges [14][15][16][17]. Some studies evaluated the effects of different wave forms on coastal decks, including unbroken, breaking and post-breaking waves and bores [14,18], and revealed fundamental differences in the effects caused by the two wave types.…”
Section: Introductionmentioning
confidence: 99%
“…Palermo et al [10] described the tsunami-induced force components on nearshore structures and reported that the hydrodynamic and surge components were a function of the instantaneous velocity and water depth. Other studies focused on the experimental testing of tsunami bore loads on rectangular buildings [11], piloti-type buildings [12], walls with overhangs [13] and coastal bridges [14][15][16][17]. Some studies evaluated the effects of different wave forms on coastal decks, including unbroken, breaking and post-breaking waves and bores [14,18], and revealed fundamental differences in the effects caused by the two wave types.…”
Section: Introductionmentioning
confidence: 99%